1997
DOI: 10.1111/j.1479-828x.1997.tb02451.x
|View full text |Cite
|
Sign up to set email alerts
|

Training, Skills and Approach to High‐risk Obstetrics in Rural GP Obstetricians

Abstract: One hundred and sixty seven (82%) of the 204 practising South Australian rural GP obstetricians responded to a questionnaire on training, skills and approach to high-risk obstetrics. The mean length of training was 8.5 months; 78% of GP obstetricians held a diploma. There was a mean of 13 years experience and 22 deliveries per year. However, 26.3% of practitioners had stopped obstetrics in the previous 12 months and cited indemnity insurance and lifestyle factors as the main reason for stopping. The GPs practi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 5 publications
1
6
0
Order By: Relevance
“…In rural Western Australia in the mid-1990s, 62% of GPs reported providing obstetrical care, and 46% had performed a C-section in the previous year 58 . Similar rates of C-section participation were found in the rural areas of southern Australia (43%) 59 and in the Australia state of New South Wales (41%) 60 . In a study of family practice graduates in Alberta from 1985 to 1995 it was found that 78% of those practicing in rural areas performed deliveries, compared to just 53% of graduates in metropolitan practice 61 .…”
Section: Workforce: Training and Case MIXsupporting
confidence: 69%
“…In rural Western Australia in the mid-1990s, 62% of GPs reported providing obstetrical care, and 46% had performed a C-section in the previous year 58 . Similar rates of C-section participation were found in the rural areas of southern Australia (43%) 59 and in the Australia state of New South Wales (41%) 60 . In a study of family practice graduates in Alberta from 1985 to 1995 it was found that 78% of those practicing in rural areas performed deliveries, compared to just 53% of graduates in metropolitan practice 61 .…”
Section: Workforce: Training and Case MIXsupporting
confidence: 69%
“…The majority of them, 83% had completed some formal postgraduate training in obstetrics, including performing Caesarean sections and using forceps and ventouse [36]. As in many other countries, the number of GPs providing intrapartum care declined significantly, with rising indemnity insurance, lifestyle issues and poor remuneration being the most important reasons for ceasing obstetrics [37]. In New Zealand, legislative changes in 1990 established independent midwifery within the health care system.…”
Section: Australia and New Zealandmentioning
confidence: 99%
“…Factors contributing to the forecast deficit in GP obstetric services included a rise in specialisation, centralisation of services, concerns regarding indemnity and litigation, rural workload and difficulty maintaining competence 9 , 10 . ‐ 13 The problem of maintaining competence in rural environments has been compounded by reported difficulties in accessing appropriate locum coverage to allow attendance at upskilling courses, in addition to the time and travel required to participate 10 …”
mentioning
confidence: 99%
“…9 Factors contributing to the forecast deficit in GP obstetric services included a rise in specialisation, centralisation of services, concerns regarding indemnity and litigation, rural workload and difficulty maintaining competence. 9,[10][11][12][13] The problem of maintaining competence in rural environments has been compounded by reported difficulties in accessing appropriate locum coverage to allow attendance at upskilling courses, in addition to the time and travel required to participate. 10 The impending shortage of GP obstetricians and the need for strategies to train, retrain and retain GP obstetricians in rural practice have been the integral considerations in developing a comprehensive training and support program offered in the Gippsland region of rural Victoria.…”
mentioning
confidence: 99%